Developing Qualitative Indicators for Journal Evaluation: Case Study of Library Science Journals of SAARC Countries - Vishwakarma, Priyanka; Mukherjee, Bhaskar (DESIDOC Journal of Library & Information Technology, 2014)
The purpose of this paper was to identify the existing criteria of various conventional databases that are considered in evaluating journals in the scholarship of library & information science (LIS) journals and accordingly developed a tool box to evaluate some selected journals of LIS in South Asian Association of Regional Cooperation (SAARC) countries. Journals have been evaluated by applying 30 criteria based on the current measures used by Thompson Reuter, SCOPUS, SciELO, LISA, LISTA, etc. The result indicates that although there are a considerable number of journals being published in India since long time, only a few journals are qualitatively strong. The review policy as mentioned in documentation, subject coverage can be considered as their strength, the geographic non-diversity of members in Editorial Board, contributors are their weakness. Most of journals are indexed in LISA and LISTA, however no journals are yet to include in JCR. Overall, to cope-up with international standard journals need to consider their publication policy thoroughly. The findings of the study seems to be useful for (a) academics – to know the list of journals which adhere to the quality requirements of LIS discipline; (b) librarians – to know the core LIS journals of SAARC countries in LIS discipline for their clients; (c) policy makers – to measure the weightage of publication, while evaluating performance for career and promotion, to evaluate individual research performance, while releasing grants for academic projects. DESIDOC Journal of Library & Information Technology, 2014, 34(2), pp. 152-161. http://dx.doi.org/10.14429/djlit.34.4968